HUBUNGAN KEADILAN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KEPUASAN KERJA DAN SPIRITUAL KERJA (STUDI MEDIA MASSA DI PEKAN BARU) - Asdiki, Muhammad; Isyandi, Isyandi (Jurnal Tepak Manajemen Bisnis, 2016)
The relationship of organizationaljustice on Organizational Citizenship Behavior through job satisfaction and workingspiritual (Studies Massa Media Pekan Baru ). under the guidance of Prof. Dr. H. B.Isyandi, SE, MS and Dr. Hj. Sri Indarti, SE, M.Si. The purpose of research to ananlyze theorganizational justice have a relationship on Organizational citizenship behavior (OCB)through job satisfaction and working spiritual view of organizational justice have arelationship on Organizational Citizenship Behavior and job satisfaction. Then to identifythe effects satisfaction workplace by spiritual work against Organizational citizenshipbehavior (OCB) and satisfaction work in the media pekanbaru.The samples are 116employees of the editorial teams of both companies News Media in the Pekanbaru. ModelPLS (Partial Least Square) . Criteria testing is look at the Outer Model which saw thevalue of Convergent Validity , Discriminant Validity, Composite Reliability, AverageVariance Extracted (AVE). Cronbach Alpha. Then examination nfluence the saw the valueestimate for path coefficients, prediction relevance ( q square ).Based on the resultsrepresent that show that justice organizational significant relationship on Organizationalcitizenship behavior (OCB) through job satisfaction and fairness of organizationalsignificant relationship to job satisfaction and fairness of organizational did not have arelationship insignificant partially in the Haluan Riau, still has a significant relationshippartially in Tribune Pekanbaru, Then the spiritual influence job satisfaction through workon Organizational citizenship behavior (OCB) has significant influence in the mediaPekanbaru.Further research who up the theme in the same the need for a spot of companypertaining to teamwork to organizational citizenship behavior (OCB), so that the resultswill be significant, spiritual work is the discussion that is dealt with today concerns theworld of work today so spiritual work needs to be added in the research that will provide agood acyl or behavior that will lead to maintain the organization .behavior ,spiritual work